2013
DOI: 10.1080/13548506.2012.701752
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategy in adolescents with premenstrual syndrome: Application of the Construal Level Theory and the Precaution Adoption Process Model

Abstract: This study aimed to apply the construal level theory (CLT) to increase the relaxation adoption as a coping behavior in adolescents with premenstrual syndrome (PMS). The theory offers a framework that assumes decision-making about adoption of any given behavior depends on perceived temporal distance from the desired or recommended behavior and thus individual might perceive any information or intervention, at two levels (low or high). In doing so, a trial was conducted on 1578 high school students suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…relaxation skills) (Delara et al . , Ussher & Perz ) or types of coping strategies (Ussher & Perz , Read et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…relaxation skills) (Delara et al . , Ussher & Perz ) or types of coping strategies (Ussher & Perz , Read et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that influencing one’s mind-set might be successfully applied as an intervention supporting trade-offs between actions that should be done and actions that are desirable. The effectiveness of these kinds of interventions has been demonstrated in various domains, such as promoting reduction of smoking [ 54 ], encouraging more positive recycling intentions [ 55 ], maximising goal-related behavior in the environmental domain [ 56 ] and increasing the adoption of relaxation as a coping behavior [ 57 ]. In the domain of personal finances, a construal level intervention was shown to promote a later planned retirement age [ 58 ].…”
Section: Current Researchmentioning
confidence: 99%
“…The Precaution Adoption Process Model (PAPM) [ 34 , 35 ] was used to determine stage of precaution adoption for each older driver allowing the educator to tailor the education to meet the needs of the driver. Utility of the PAPM framework has been shown in previous studies of health-behaviour adoption [ 34 , 38 40 ] and paediatric injury prevention [ 41 ]. It has also been used to explore the process of driving cessation and self-regulation among older drivers [ 42 ].…”
Section: Introductionmentioning
confidence: 95%